Sum-capacity of D2D and cellular hybrid networks over cooperation and non-cooperation - Ziyang Liu; Tao Peng; Bo Peng; Wenbo Wang (2012 7th International ICST Conference on Communications and Networking in China, 2012)
This paper analyzes the effect of cooperation on the network capacity in hybrid network composed of cellular and D2D communications. The D2D communication shares uplink resource with cellular user and we consider a simple system model which contains one D2D pair and one cellular user. First we derive out the cumulative distribution function (CDF) of the interference at the receiver in the dual interference channel. Then we study the network capacity based on the former corollary in different scenarios according to the CSI acknowledgement at the transceiver case by case. The simulation results show that the cooperation between cellular and D2D link can bring obvious contribution to the sum capacity of hybrid network. When the transmit power of the transmitter of the D2D and cellular network is large, the hybrid network is interference limited and the capacity with cooperation between transmitter and receiver is better than case without cooperation but there are no difference between different kinds of cooperation between links. While, if output power is low and the hybrid network is part of noise limited, the network capacity is growing with acknowledgement of CSI. Specially, if the cooperation is between transceivers but not links, the network capacity may be suffer loss for greedy of links.